PENGARUH TINGKAT PARTISIPASI PEREMPUAN DALAM BERWIRAUSAHA TERHADAP TINGKAT SOSIAL EKONOMI KELUARGA (Studi di Desa Labuhan Ijuk Kecamatan Moyo Hilir) - Marisa Sutanty; Sri Rahayu; Maya Insani (Fakultas Ekonomi dan Manajemen, 2022)
The purpose of this study was to determine the effect of the level of women's participation in entrepreneurship on the socioeconomic level of the family in Labuhan Ijuk Village, Moyo Hilir Sub-District. This type of research is associative research. The population in this study are women who run entrepreneurship in Labuhan Ijuk Village, Moyo Hilir Sub-District, amounting to 64 people. Determination of the sample using a saturated sample, ie all the population is used as a sample. The tool used to collect data is by using a questionnaire. Data analysis was performed using simple linear regression analysis, t test and coefficient of determination (R2). The results of this study indicate that the level of women's participation in entrepreneurship has a positive and significant impact on the socioeconomic level of the family in Labuhan Ijuk Village, Moyo Hilir Sub-District. This means that the high socioeconomic level of the family in Labuhan Ijuk Village, Moyo Hilir Sub-District is influenced by the high level of women's participation in entrepreneurship in helping the family economy. The degree of influence of the variable level of women's participation in entrepreneurship on the socio-economic level of the family in Labuhan Ijuk Village, Moyo Hilir Sub-District is 86%, while the remaining 14% is influenced by other variables outside this research model.